A Conflictive Solidarity: Chile Facing the Second Independence War of Cuba (1895-1898) (Palimpsesto, 2017)
A prominent solidarity movement developed in Chile supporting the Cuban independence uprising that began in 1895. However, this movement collided with the Chilean government’s rejection to their demonstrations. Through the press records of those times and other sources, the circumstances of this collision are analyzed, which made evident the existence of two different visions about the concept of nation in Chile. One of them had been developed and applied by those who were leading the country’s affairs, the other emerged from a diverse community but subordinated to the power of the former ones, which nevertheless managed temporarily to make it visible through their solidarity actions for Cuba.
Keywords: Nation; Solidarity; Cuba; Independence; Americanism